CONSUMPTION OF ULTRA-PROCESSED FOODS BY CHILDREN UNDER 24 MONTHS OF AGE AND ASSOCIATED FACTORS - Lopes,Wanessa Casteluber (2020)
ABSTRACT Objective: To evaluate the intake of ultra-processed foods by children under 24 months of age from the city of Montes Claros and identify factors associated with this consumption. Methods: This is a population-based cross-sectional study with data collected from households through interviews. A questionnaire assessed the sociodemographic conditions of the family, maternal and child characteristics, and food consumption. We adopted a multivariate model to identify factors associated with the intake of ultra-processed foods. Results: A total of 545 children participated in this study, of whom 74.3% consumed some kind of ultra-processed food. The factors most strongly associated with this consumption were children older than six months, infants who were not breastfed, households with up to three residents, and the main caregiver of the child being someone other than the mother. Conclusions: Children under 24 months start consuming ultra-processed products at an early age, replacing foods considered natural and healthy. This study can contribute to guide health professionals in counseling families about feeding in the first years of life, emphasizing the proper introduction of complementary feeding and discouraging the consumption of ultra-processed products.